Public provision, commodity demand and hours of work: An empirical analysis - Jukka Pirttilä; Ilpo Suoniemi (Center for Economic Studies and ifo Institute (CESifo), 2010)
Atkinson and Stiglitz (Journal of Public Economics 1976) show that when the government has access to non-linear income taxation and consumer preferences are separable between consumption and leisure, there is no need for differentiated commodity taxation. This paper examines the empirical validity of this claim using consumption data from Finland. The data have extensive information on commodity demand, the use of public services and hours of work. When labour income is controlled for in a semi-parametric way, we find that capital income and housing expenses are negatively associated with hours of work, whereas the use of child care is somewhat positively correlated with labour supply. These results suggest that capital income and housing should be taxed whereas day care could perhaps be subsidised.
Keywords: C14; H21; H42; 330; commodity taxation; public provision of private goods; semi-parametric methods; Verbrauchsteuer; Optimale Besteuerung; Arbeitsangebot; Arbeitszeit; Zeitallokation; Kinderbetreuung; Subvention; Kapitalertragsteuer; Grundsteuer; Schätzung; Finnland